Changes in employment psychology of Chinese university students during the two stages of COVID-19 control and their impacts on their employment intentions - Zheng, Sining; Yan, Yanfen (Frontiers in Psychology, 2024)
The employment psychology and issues being faced by university students have garnered significant attention after the COVID-19 outbreak. Focusing on Chinese university students, this study compares the changes in their employment psychology between the initial and normalization stages of COVID-19 prevention and control in China and examines their employment choices during the normalization stage. This study also investigates how the transformed employment psychology of these students influences their employment intentions. Results show that: (1) Chinese university students exhibit stronger feelings of employment confusion, anxiety, stability preference, uneasiness, and inferiority during the normalization stage compared with the initial stage, thus leading to a more negative employment psychology; (2) during the normalization stage, university students display a more pessimistic outlook on their employment situation and show their preference for direct employment, particularly in public institutions, state-owned enterprises, and government organizations. They also show a greater interest in working in first-tier cities than in their hometowns; (3) the employment psychology of these students in the post-pandemic period significantly influences their employment intentions, with employment stability preference psychology playing a crucial role; and (4) the employment stability preference psychology positively and significantly affects the employment intentions of junior college students. Conversely, this employment stability preference psychology has a negative effect on the employment intentions of academic master's and doctoral students. This paper also proposes some strategies to enhance the employment psychology of university students and improve their quality of employment at various levels, including government, school, enterprise, family, and individual.